2012
DOI: 10.1200/jco.2011.41.2395
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Therapy Using Belinostat for Patients With Unresectable Hepatocellular Carcinoma: A Multicenter Phase I/II Study With Biomarker and Pharmacokinetic Analysis of Tumors From Patients in the Mayo Phase II Consortium and the Cancer Therapeutics Research Group

Abstract: A B S T R A C T PurposeEpigenetic aberrations have been reported in hepatocellular carcinoma (HCC). In this study of patients with unresectable HCC and chronic liver disease, epigenetic therapy with the histone deacetylase inhibitor belinostat was assessed. The objectives were to determine dose-limiting toxicity and maximum-tolerated dose (MTD), to assess pharmacokinetics in phase I, and to assess activity of and explore potential biomarkers for response in phase II. Patients and MethodsMajor eligibility crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(138 citation statements)
references
References 31 publications
4
133
0
1
Order By: Relevance
“…The progression-free and overall survival was 2.6 and 6.6 months, respectively. Epigenetic therapy with belinostat displayed well-tolerated and disease stabilization, and more studies are needed to further determine the efficacy and benefits with belinostat treatment in HCC patients (119). Obviously, questions remain regarding whether epigenetic therapy alone or in combination with conventional chemotherapy will be more effective in eradicating T-IC than currently available adjuvant therapeutics for the improvement of therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The progression-free and overall survival was 2.6 and 6.6 months, respectively. Epigenetic therapy with belinostat displayed well-tolerated and disease stabilization, and more studies are needed to further determine the efficacy and benefits with belinostat treatment in HCC patients (119). Obviously, questions remain regarding whether epigenetic therapy alone or in combination with conventional chemotherapy will be more effective in eradicating T-IC than currently available adjuvant therapeutics for the improvement of therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical investigation, belinostat inhibited cell growth in a HCC cell line, whereas vorinostat sensitized HCC cells to acetylation of p53 and TNF-related apoptosis-inducing ligand (TRAIL)-induced apoptosis [69]. Moreover, in a multi-center phase I/II clinical trial, belinostat was found to stabilize inoperable advanced HCC [105]. Furthermore, Lin et al [106] reported that HDAC inhibitors induced cell death may be accompanied with simultaneously activating tumor-progression genes.…”
Section: Histone Deacetylase (Hdac) Inhibitorsmentioning
confidence: 99%
“…On the other hand, brivanib, which targets VEGFR, PDGFR and FGFR, also failed to prolong OS (Table 1) in a phase III trial conducted to investigate its efficacy as a first line therapy even though it had a more favorable toxicity profile than sorafenib [89,90]. Moreover, another phase III, randomized, placebo-controlled study investigated the efficacy of brivanib after sorafenib failure and the authors reported that, in comparison to placebo, brivanib resulted in a longer median TTP but insignificant increase in the OS (Table 1) [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108].…”
Section: Anti-angiogenic Agentsmentioning
confidence: 99%
“…Belinostat is a novel pandeacetylase inhibitor that has been clinically tested in patients with solid tumors, such as liver cancer (9), ovarian cancer (10), malignant pleural mesothelioma (11) and thymic epithelial tumors (12), as well as in patients with hematological malignancies (13,14). Favorable antineoplastic effects of belinostat in combination with bortezomib have been reported (15)(16)(17)(18), however, there has been no study evaluating the effect of the combination on renal cancer cells and investigating ER stress induction as a mechanism of action.…”
Section: Introductionmentioning
confidence: 99%